ANESTHETIC SUPPORT FOR THE CORRECTION OF RECTAL AND ANAL ATRESIA IN CHILDREN - Dusyarov J.T. Khudoykulov T.M. Kalkonov B.I. Igamova S.S. (International Multidisciplinary Journal for Research & Development, 2024)
This article reviews the current literature on anesthetic support for the correction of rectal and anal atresia in children, focusing on preoperative assessment, intraoperative considerations, and postoperative care. The importance of a multidisciplinary approach involving pediatric surgeons, anesthesiologists, and other healthcare providers is emphasized to optimize outcomes for these complex cases. Various anesthetic techniques, monitoring modalities, and perioperative strategies are discussed to provide comprehensive support for children undergoing surgery for rectal and anal atresia. Additionally, potential challenges and complications associated with anesthesia in this patient population are addressed, along with recommendations for their management.